Antimicrobial Susceptibility Pattern of Urinary Bacterial Isolates – Local experience at Rawalpindi, Pakistan - Sattar, Abdul; Ghuman, Zafar Iqbal; Sattar, Azfar (Infectious Diseases Journal of Pakistan, 2023)
Background: Bacteria are the most common cause of urinary tract infections in all age groups. Drug resistance is rising in uropathogens worldwide, highlighting the importance of local antibiotic susceptibility patterns. We have aimed to determine the antimicrobial susceptibility pattern of uropathogens isolates among in and outdoor patients referred to CITI Lab (private sector) Rawalpindi. Methods: A retrospective review of lab records of 3802 urine samples processed from Jan. 2010 to Dec. 2010 was reviewed. Urine culture was performed using conventional microbiological techniques. Biochemical testing was used to identify the organisms and antibiotic sensitivity was done by the modified Kirby Bauer method as per Clinical Laboratory Standards Institute recommendations. Results: Out of total 3802 urine samples 2244 (59%) were culture negative, whereas significant isolates were obtained in 1368 (36%) samples and mixed growth (more than two organisms) was obtained in 190 (5%). Out of these significant isolates, 123 (9%) were Candida species and 1245 (91%) were bacterial isolates. Escherichia coli (70%) was the most common isolate followed by Klebsiella pneumoniae (15%). Imipenem/ meropenem, amikacin, cefoperazon-sulbactam, pipracillintazobactam and nitrofurontoin were sensitive to more than 85% of isolates while fluroquinolones, amoxi-clave, cotrimaxazole and ampicillin were sensitive to less than 40% of isolates. Conclusion: More than 60% of uropathogens are resistant to conventional oral antibiotics like fluroquinolones and cotrimaxazole limiting to injectable antibiotics. Nitrofurontoin is the only oral antibiotic left which is affective. Key words: Antibiotics, Drug resistance, Urinary tract infections, Uropathogens